Penerapan Algoritma C4.5 terhadap Pengaruh VSTOCK.ID pada Masyarakat di Masa Pandemi Covid-19 - Michael Sitorus; Vanesa (Journal of Informatics and Advanced Computing (JIAC), 2021)
The Covid-19 Pandemic Outbreak, is an international disaster that has shaken all aspects of life, including the business world. With the Covid-19 outbreak, automatically there will be no face-to-face meetings to avoid the spread of Covid-19, or at least minimizing meetings. Vstock.id's business problems that arise in society are the way Vstock.id conducts activities to disseminate information to its consumers, because many consumers have doubts about the original brand of a product and service or facility made by Vstock.id and the level of consumer satisfaction during the Covid-19 period. The main goal in establishing Vstock.id is to provide an average price without setting a high price but in accordance with proportional quality such as high quality, original, branded and can be purchased by all groups even though branded products, so that all people can feel the fashion bar brands in the future. now. Vstock.id's business concept is with quality clothing trends, trend brands, quality materials, original brands, and prices that are much cheaper than market store prices. This business conclusion shows that the order of attributes that have the highest level of importance in Vstock.id business development is clothing trends, quality of materials, brand trends, original or original brands and the last is price. The advice that can be given is the development of fashion trends that exist in the following year or now which must be based on the formation of a brand, quality and price to make Vstock.id's business as well as the product ideal. Where the ideal products and businesses that match consumer preferences for the development of Vstock.id are branded or branded goods with original quality such as buying from a store but below the market store selling price with quality control check Product selling price starts from IDR. 80,000 - 300,000.